(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
Repeat breeding (RP) is a one of the most significant problem in dairy cattle because it increased production cost of insemination, treatment, feed, labor and management and also increased calving interval with decreased milk production. This study was conducted at the different Bathan areas of Shahjadpur Upazila under Sirajgonj district. The total of 30 repeat breeder cows was selected randomly to determine their reproductive hormonal profile before and after synchronization at the selected areas and repeat breeder cows were marked by ear tag and collected breeding history of each individual cow. All experimental RP were synchronized by the administration of GnRH (day- 0), PGF2α (day-7) and Artificial Insemination (AI) with GnRH (day-9). Blood samples were collected before and after synchronization during standing heat period of estrous cycle of each cow. The total experiment was done and analyzed in the laboratory by using endocrine detection kits (Mono LelacR USA). This present study revealed that the level of luteinizing hormone (LH), follicle stimulating hormone (FSH), progesterone (P4) were significantly differed between repeat breeder cows and synchronized repeat breeder cows. These findings clearly indicated that reproductive hormonal aberrations might be one of the major causes of repeat breeding in Baghabari milk shed areas. Asian Australas. J. Biosci. Biotechnol. 2018, 3 (3), 237-240